2014
DOI: 10.1186/2046-4053-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and protocol for a systematic review and meta-analysis on reduced data gathering in people with delusions

Abstract: BackgroundThe tendency to form conclusions based on limited evidence is known as the ‘jumping to conclusions’ (JTC) bias, and has been a much studied phenomena in individuals with psychosis. Previous reviews have supported the hypothesis that a JTC bias is particularly linked to the formation and maintenance of delusions. A new systematic review is required as a number of studies have since been published, and older reviews are limited by not systematically assessing methodological quality or the role of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Such a possibility is consistent with one of the larger beads task studies included in our meta-analysis, which found no evidence for an association between paranoia (in the context of paranoid delusions) and jumping to conclusions once the association between paranoia and general cognitive performance had been controlled for. 47 We anticipate that the upcoming meta-analysis by Taylor et al 34 will help clarify because they aim to quantify differences in data gathering between groups with delusions and control groups while exploring a variety of potential moderating variables.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a possibility is consistent with one of the larger beads task studies included in our meta-analysis, which found no evidence for an association between paranoia (in the context of paranoid delusions) and jumping to conclusions once the association between paranoia and general cognitive performance had been controlled for. 47 We anticipate that the upcoming meta-analysis by Taylor et al 34 will help clarify because they aim to quantify differences in data gathering between groups with delusions and control groups while exploring a variety of potential moderating variables.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…79 Third, the beads task is rarely incentivised and motivation might explain some differences in performance. 80,81 We suggest that further progress in determining whether people with delusions jump to conclusions could be made by using meta-analysis to investigate between-group differences in beads task performance, 34 exploring new data-gathering paradigms that might overcome methodological limitations of the beads task, [80][81][82][83][84][85][86] examining more closely what evidence is available to participants at the point when they decide to stop drawing beads, 87 controlling for important aspects of individual variation, 47 and revisiting the original-and methodologically sophisticatedbeads task paradigm. 1…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, only 22 clinical and nonclinical samples, mostly with small sample sizes, were included. More importantly, they included studies regardless of their methodological quality and combined non-independent effects (using 47 effect sizes from 22 samples) (Ross, McKay, Coltheart, & Langdon, 2015;Taylor, Hutton, & Dudley, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additional studies were manually searched from the reference lists of the identified papers, as well as relevant review and meta-analytic papers (Fine et al, 2007;Garety & Freeman, 2013;Ross et al, 2015;Taylor et al, 2014). To further identify any studies that potentially slipped through the above search procedure, we emailed authors of the articles included in the primary search for any recently published studies.…”
Section: Identification Of Studiesmentioning
confidence: 99%